Mycobacterium gordonae Isolation in Oregon, 2005–2012. (4th October 2017) - Varley, Cara; Henkle, Emily; Winthrop, Kevin L
Abstract: Background: Mycobacterium gordonae (M. gordonae) is one of the slow growing mycobacteria, often considered a contaminant and rarely pathogenic. It is often associated with pseudo-outbreaks or infections, usually from a water source; however pulmonary, skin and soft tissue and disseminated infections have been reported in both immunocompetent and immunocompromised hosts. We describe a cohort of patients from Oregon who isolated M. gordonae from > 1 pulmonary specimen. Methods: Oregon residents with M. gordonae isolation were identified from all NTM isolates collected 2005–2012 for statewide laboratory surveillance by the Oregon Health Authority. Clinical data was reviewed for the subset with mycobacterial cultures 2005–2006. We performed descriptive analyses, compared categorical variables in univariate fashion by the χ2 test. Student's t test or Wilcoxon rank-sum test (WRS) was used to evaluate continuous variables. Results: 457 patients isolated M. gordonae > 1 time between 2007 and 2012 in Oregon, 88 (19.3%) of those also isolated another NTM species and half ( N = 46) met ATS/IDSA case definition for NTM disease. 237 (51.9%) patients had > 2 M. gordonae isolates. Only 19 of 457 (4.2%) of those that isolated M. gordonae did so before isolating another species of NTM; 6 (31.6%) subsequently met NTM disease criteria. Median time from first M. gordonae isolation to the first isolation of another NTM species was 56 days (range 1–1146 days). Median number of M. gordonae positive specimens was 1 (range 1–6). There was no statistically significant difference in gender or age in those who isolated another NTM species or had NTM disease with M. gordonae isolation. Higher number of positive M. gordonae isolates were associated with isolation of another NTM species (WRS P < 0.01) but not with NTM cases (WRS P = 0.09). Between 2005 and 2006, 33 patients isolated M. gordonae ; 4 had > 2 M. gordonae positive isolates and 3 met criteria for NTM disease. Median age was 66 years (range 27–88), 27.3% female and 27 (81.8%) had radiographic findings consistent with pulmonary NTM. Conclusion: Approximately 20% of our cohort of patients with pulmonary M. gordonae isolates, also isolated a pathogenic NTM species. Further research is needed to evaluate the outcomes of those with NTM disease and M. gordonae isolation. Disclosures: All authors: No reported disclosures.